2021
DOI: 10.3390/ani11071912
|View full text |Cite
|
Sign up to set email alerts
|

Using Omics Approaches in the Discovery of Biomarkers for Early Diagnosis of Johne’s Disease in Sheep and Goats

Abstract: Johne’s disease (JD) is caused by Mycobacterium avium subsp. paratuberculosis (MAP) and is an important and emerging problem in livestock; therefore, its control and prevention is a priority to reduce economic losses and health risks. Most JD research has been carried out on cattle, but interest in the pathogenesis and diagnosis of this disease in sheep and goats is greatest in developing countries. Sheep and goats are also a relevant part of livestock production in Europe and Australia, and these species prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 163 publications
(225 reference statements)
0
3
0
Order By: Relevance
“…Changes in TLR gene expression in sheep at the time of experimental infection with MAP have been observed in both in vitro and in vivo experiments (Plain et al, 2010). TLR2 regulates the specific immune system in the initial phases of JD and influences development of disease in selected tissues and in sheep PBMCs (Fiorentina et al, 2021). TLR2 mRNA expression rises in the multibacillary form of JD, owing to a stronger inflammatory response in regions at which the majority of microbes are located (Nalubamba et al, 2008).…”
Section: Toll Like Receptors (Tlrs)mentioning
confidence: 99%
“…Changes in TLR gene expression in sheep at the time of experimental infection with MAP have been observed in both in vitro and in vivo experiments (Plain et al, 2010). TLR2 regulates the specific immune system in the initial phases of JD and influences development of disease in selected tissues and in sheep PBMCs (Fiorentina et al, 2021). TLR2 mRNA expression rises in the multibacillary form of JD, owing to a stronger inflammatory response in regions at which the majority of microbes are located (Nalubamba et al, 2008).…”
Section: Toll Like Receptors (Tlrs)mentioning
confidence: 99%
“…A genome‐wide association study (GWAS) in Garfagnina goats identified several regions associated with serological response to MAP (Cecchi et al, 2017). In addition to the GWAS, RNAseq and MicroRNA sequencing studies in cattle have identified expression patterns associated with JD progression and have suggested their potential as diagnostic tools (Casey et al, 2015; Fiorentina et al, 2021; Malvisi et al, 2016, 2020; Marino et al, 2017). The extension of these studies to goats is of interest considering the differences in progression of the disease among species.…”
Section: Introductionmentioning
confidence: 99%
“…An economic study showed that MAP infection reduced the profit efficiency from 84% to 64% in Italian dairy sheep and goat farms [ 8 ]. Other countries and regions have also shown varying degrees of economic losses as a result of PTB [ 9 ].…”
Section: Introductionmentioning
confidence: 99%